2022
DOI: 10.1111/jth.15748
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusion and anticoagulation in hematological cancer‐associated thrombosis and thrombocytopenia: The CAVEaT multicenter prospective cohort

Abstract: Background Venous thromboembolism (VTE) in patients with thrombocytopenia represents a complex management challenge. Objectives To describe practice, document outcomes, and compare management to national guidelines. Methods We present a prospective multicenter cohort of 105 patients with hematological cancer, VTE within 28 days, and platelets <50 × 109/L from May 14, 2019 to April 24, 2021 from 20 sites. Results Median age was 64 and median initial platelet count 28 × 109/L. Thromboses were: 46% catheter‐assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Two international studies have recently demonstrated the heterogeneity in the management of this cohort, the key findings of which are summarized in Table 2. 23,24 The Cancer-Associated Venous Thrombosis and Thrombocytopenia (CAVEaT) UK study in patients with hematological malignancies showed that 47% of patients with higher risk thrombosis and 5% with lower risk thrombosis were managed according to the ISTH guidance. There was variation in the use of platelet transfusions.…”
Section: What Is the Current Practice?mentioning
confidence: 99%
See 1 more Smart Citation
“…Two international studies have recently demonstrated the heterogeneity in the management of this cohort, the key findings of which are summarized in Table 2. 23,24 The Cancer-Associated Venous Thrombosis and Thrombocytopenia (CAVEaT) UK study in patients with hematological malignancies showed that 47% of patients with higher risk thrombosis and 5% with lower risk thrombosis were managed according to the ISTH guidance. There was variation in the use of platelet transfusions.…”
Section: What Is the Current Practice?mentioning
confidence: 99%
“…Changes in anticoagulation were observed in 51% of patients by 90 days. Mortality was 15% at 28 days and significant morbidity was 24 The North American Thrombocytopenia Related Outcomes with Venous thromboembolism (TROVE) study also found that changes in anticoagulation choice were frequent, with less frequent alterations in anticoagulation intensity. 23 Interestingly, the two studies revealed different findings.…”
Section: What Is the Current Practice?mentioning
confidence: 99%
“…Extrapolated, this supports annual cost‐savings of over £1 million per year in England 7 . The second flash‐mob audit looked at care and outcomes of patients with thrombotic thrombocytopenic purpura and has generated data that has been used to support the commissioning of specialist centers across the United Kingdom 14 . The third flash‐mob project is in late development and will audit the real‐world use of reversal agents for direct oral anticoagulants.…”
Section: Title Year Authors/collaborators Study Participants Type Of ...mentioning
confidence: 99%
“… 7 The second flash-mob audit looked at care and outcomes of patients with thrombotic thrombocytopenic purpura and has generated data that has been used to support the commissioning of specialist centers across the United Kingdom. 14 The third flash-mob project is in late development and will audit the real-world use of reversal agents for direct oral anticoagulants. This project has attracted nearly £100,000 funding from industry in the form of academic grants and administration support.…”
mentioning
confidence: 99%
“…Although platelet transfusion is essential for preventing or treating bleeding, 9 , 10 the cost of platelet products is high, and unnecessary frequent platelet transfusions may increase the risk of transfusion reactions. 11 , 12 , 13 , 14 , 15 , 16 , 17 Therefore, it is necessary to comprehensively analyze and monitor the proper use of platelets.…”
Section: Introductionmentioning
confidence: 99%